Undergraduate speech-language therapy students’ perceived competence to treat persons who stutter following an additional training component using a simulated patient - Vermeulen, Carianne (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Centre for Health Sciences Education)--University of Stellenbosch, 2010.